2019
DOI: 10.5115/acb.19.050
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of glucosamine and risedronate (alone or in combination) against osteoarthritic changes in rat experimental model of immobilized knee

Abstract: This study is aiming to investigate the protective effect of glucosamine, risedronate (alone or in combination) on articular cartilage in experimental model of immobilized rat knee. Twenty-five adult male albino rats were divided into five groups (five rats each): control group, immobilized group, glucosamine-treated group, risedronate-treated group, and group treated by a combination of glucosamine and risedronate. The articular cartilage was obtained for histological, immunohistochemical and morphometric stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…This supports the findings of other preclinical studies, which did not find any chondroprotective effect of BP treatment on articular cartilage damage score either (12,14). On the other hand, some authors reported a significant positive effect of bisphosphonates on OA severity scores, showing fewer degenerative changes compared to the untreated animals (3,10,13,17,19,49,50). Moreover, a previous study of our research group, has shown a modest chondroprotective effect with short-term risedronate administration (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports the findings of other preclinical studies, which did not find any chondroprotective effect of BP treatment on articular cartilage damage score either (12,14). On the other hand, some authors reported a significant positive effect of bisphosphonates on OA severity scores, showing fewer degenerative changes compared to the untreated animals (3,10,13,17,19,49,50). Moreover, a previous study of our research group, has shown a modest chondroprotective effect with short-term risedronate administration (24).…”
Section: Discussionsupporting
confidence: 89%
“…It is believed that bisphosphonates could modulate the subchondral bone remodeling and consequently inducing changes in the OA progression, reducing the cartilage degeneration ( 3 , 10 , 13 , 18 20 , 49 ). In previous preclinical studies, risedronate has shown a reduction in the cartilage pathology ( 50 ) and changes in cancellous bone microarchitecture leading to improved mechanical properties ( 17 , 23 , 24 ). However, contradictory results in clinical trials hindered their acceptation regarding the disease-modifying efficacy in the scientific community ( 15 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The untreated OA group had thinned articular cartilage with surface abrasions. This was coupled with the observation of disorganized chondrocytes and depletion of proteoglycan (Lu et al 2018 ; Salman et al 2019 ). The total modified Mankin score given upon assessment of the articular cartilage of knee joint safranin-O-fast green stained sections was significantly increased in OA rats as compared to normal rats, indicating the occurrence of cartilage erosion and decrease in proteoglycan content (Jeong et al 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the combination of nutraceutical and other therapies and drugs was also investigated. In this context beneficial effects were observed in the association of glucosamine and risedronate [31,36], glucosamine and fish collagen peptide [37] and glucosamine hydrochloride and chondroitin sulfate plus fursultiamine, where only the combined group with the addition of the vitamin showed a significant chondroprotective effect [39]. Furthermore, in one study using an OA experimental model in rats, enhanced responses were observed with the association of glucosamine sulfate, chondroitin sulfate and photobiomodulation [43].…”
Section: Discussionmentioning
confidence: 96%
“…Two studies in rats [27,28] and the one which included the mice model [29] used intraarticular injections to chemically induce OA. Only two studies, one involving rabbits [30] and another involving rats [31], used physically immobilisation to induce the OA. Lastly, only one study in guinea pigs was included as a spontaneous model of OA [32].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%